From Verses to Action: Project-Based Learning in Al-Qur'an Hadith Subjects to Foster Understanding of Verses and Hadiths on Environmental Sustainability and Ecological Awareness in Madrasahs - Khalid Mawardi Khalid Mawardi; Moh. Ali (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2025)
Environmental sustainability is a critical issue that must be instilled from an early age through education, including in Qur’an-Hadith instruction. However, learning in many madrasahs still relies on conventional, cognitively oriented approaches. This condition forms the main problem of the present study, as students’ understanding of Qur’anic and Hadith texts related to the environment remains decontextualized, disconnected from real-life situations, and fails to shape ecological attitudes and behaviors. This study aims to explore the implementation of the Project-Based Learning (PjBL) model in enhancing students’ comprehension and concern for Islamic values regarding environmental preservation. This study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The research was conducted at MA YSPIS Rembang. The findings indicate that PjBL fosters active student engagement through real-life project such as creating a school garden, conducting digital awareness campaigns, and designing educational pamphlets. These activites enabled students to meaningfully connect Qur’anic and Hadith teaching with real-world environmental issues, fostering a sense of ecologial responsibility. The study concludes that PjBL is effective in internalizing Islamic environmental ethics and increasing students’ awareness and commitment to practicing these values in their daily lives.